Sexual Activities of Pre-Elderly and Elderly Women Who Visit the General and Elderly Examination Ward of the UPTD Mengwi II Public Health Center - Adnyani, Ni Putu Nuadi; Martini, Ni Made Dwi Ayu; Dewi, Si Putu Agung Ayu Pertiwi (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2024)
Background: The pre-elderly and elderly endure several changes in the function of their body systems as they get older. Changes can have an impact on parts of pre-elderly and elderly people's lives, including sexual activity. Purposes: The purpose of this study was to determine the description of the sexual activity of pre-elderly and elderly women who visit the General and Elderly Examination Ward of the UPTD Mengwi II Public Health Center. Methods: This study is a quantitative descriptive study involving 88 samples selected through the Purposive Sampling technique. Data were collected using the Female Sexual Function Index (FSFI) questionnaire. Result: The results of the study showed that the sexual activity of pre-elderly women had an average value of 56.33 which was considered not to have sexual dysfunction, while the sexual activity of elderly women had an average value of 53.79 which was considered to have sexual dysfunction (cut off point of 55). Age (p=0.020), education (p=0.003), disease history (p=0.000), menopause (p=0.000), and perception (p=0.000) are all associated with pre-elderly women's sexual engagement. Age (p=0.020), education (p=0.001), disease history (p=0.000), menopause (p=0.000), and perception (p=0.000) are all associated with senior women's sexual activity. Conclusion: Based on the research results, it was found that most of the low values in this study that led to sexual dysfunction were influenced by factors of medical history, the elderly who had mostly experienced menopause, and the understanding that engaging in sexual activity at an advanced age was considered taboo by the respondents.